International Roadshow: New Advances in Endocrinology and Metabolic Diseases - Steenblock, Charlotte; Saber-Ayad, Maha M.; Bornstein, Stefan R. (Hormone and Metabolic Research, 2024)
Dear Readers,Currently, there is a myriad of new developments in the field of endocrinology. In particular, significant strides have been made in the development of poly-agonists for the treatment of type 2 diabetes and obesity 12. Poly-agonists represent a novel therapeutic approach by combining multiple actions within a single molecule, targeting multiple receptors simultaneously to achieve enhanced efficacy. These innovative compounds aim to address the complex interplay of hormonal pathways involved in glucose regulation and metabolism, offering potential breakthroughs in the management of diabetes and obesity.